Risk Factors for Urological Complications Associated with Caesarean Section—A Case-Control Study - Viorel Dragos Radu; Anda Ioana Pristavu; Angela Vinturache; Pavel Onofrei; Demetra Gabriela Socolov; Alexandru Carauleanu; Lucian Boiculese; Sadyie Ioana Scripcariu; Radu Cristian Costache (Medicina, 2022)
Background and Objectives: Acute urologic complications, including bladder and/or ureteric injury, are rare but known events occurring at the time of caesarean section (CS). Delayed or inadequate management is associated with increased morbidity and poor long-term outcomes. We conducted this study to identify the risk factors for urologic injuries at CS in order to inform obstetricians and patients of the risks and allow management planning to mitigate these risks. Materials and Methods: We reviewed all cases of urological injuries that occurred at CS surgeries in a tertiary university centre over a period of four years, from January 2016 to December 2019. To assess the risk factors of urologic injuries, a case-control study of women undergoing caesarean delivery was designed, matched 1:3 to randomly selected women who had an uncomplicated CS. Electronic medical records and operative reports were reviewed for socio-demographic and clinical information. Descriptive and univariate analyses were used to characterize the study population and identify the risk factors for urologic complications. Results: There were 36 patients with urologic complications out of 14,340 CS patients, with an incidence of 0.25%. The patients in the case group were older, had a lower gestational age at time of delivery and their newborns had a lower birth weight. Prior CS was more prevalent among the study group (88.2 vs. 66.7%), as was the incidence of placenta accreta and central praevia. In comparison with the control group, the intraoperative blood loss was higher in the case group, although there was no difference among the two groups regarding the type of surgery (emergency vs. elective), uterine rupture, or other obstetrical indications for CS. Prior CS and caesarean hysterectomy were risk factors for urologic injuries at CS. Conclusions: The major risk factor for urological injuries at the time of CS surgery is prior CS. Among patients with previous CS, those who undergo caesarean hysterectomy for placenta previa central and placenta accreta are at higher risk of surgical haemostasis and complex urologic injuries involving the bladder and the ureters.